Effect of addition beans and clover leaves to the diet layer hens on the productivity and quality of the eggs produced - Dalla, Tawfik; abd al aziz, Fahim; Y Hoseen, Hasan (Latakia University Journal -Biological Sciences Series, 2019)
The goal of this research is to study the Effect of addition beans and clover leaves to the diet layer hens on the productivity and quality of the produced eggs, The selection criteria were: egg shell, yolk color, and weight of the egg, The research was carried out in the 2016/2017 season within a special camp for raising layer hens in Tartous. The results showed that the use of fodder additive in layer hens feed resulted in a significant increase in all studied treatments compared with the non-additive added to the feed. The treatment of M2 was the best for all studied indicators and with significant differences is the use of feed additives (7% Medicago Sativa), followed by M6 (7% Medicago Sativa+ Vicia Faba). The thickness of shell was 34.26 mm at the M2 treatment. 33.92 mm at M6 compared with non-coefficient M0 30.86 mm. The treatment of M2 was also superior to the other treatments in terms of the color yolk, where the carotene ratio was 20.445 µg /g yolk, followed by treatment M6, where the carotene was 19.848 µg /g yolk compared to the M0 non-factor 18.577 µg / g yolk. The weight of the egg exceeded the M2 treatment where the average weight of the egg was 65.452g, followed by the treatment M6 with an average weight of the egg 64.526 g, compared to the M0 non-factor 62.696 g. هدف البحث لدراسة تأثير إضافة أوراق الفصّة Medicago sativa والفول البلدي vicia faba في عليقة الدجاج البياض على مواصفات البيض الناتج. وكانت المعايير المستخدمة هي: سماكة القشرة, لون الصّفار, وزن البيضة وإنتاجية البيض. نفذ البحث في موسم 2016/2017 ضمن مدجنة خاصة لتربية الدجاج البيّاض في طرطوس. أظهرت النتائج أن استخدام الإضافة العلفية في تغذية الدجاج البياض أدت إلى زيادة معنوية في جميع المعاملات المدروسة بالمقارنة مع الشاهد غير المضاف له اية اضافة علفية, وكانت المعاملة 2M هي الأفضل بالنسبة لجميع المؤشرات المدروسة وبفروق معنوية وهي استخدام الإضافة العلفية( 7% من أوراق الفصة) تلتها المعاملة M6 وهي استخدام الإضافة العلفية (7% من خليط أوراق الفصة والفول) إذ بلغت سماكة القشرة 34.26 ملم عند المعاملة M2, تلتها 33.92 ملم عند المعاملة M6 مقارنة مع الشاهد M0 غير المُعامل 30.86 ملم. وايضا تفوقت المعاملة M2 على باقي المعاملات من حيث لون الصفار, إذ بلغت نسبة الكاروتين فيها 20.445 مكغ/غ صفار تلتها, المعاملةM6 و كانت نسبة الكاروتين 19.848 مكغ/غ صفار مقارنة بالشاهد M0 غير المُعامل 18.577 مكغ/غ صفار. وكذلك بالنسبة لوزن البيضة تفوقت المعاملة M2 اذ بلغ متوسط وزن البيضة 65.452 غ, تلتها المعاملة M6 بمتوسط لوزن البيضة 64.526 غ مقارنة بالشاهد M0 غير المُعامل 62.696 غ .